ANALISIS KEPEMIMPINAN DI INDONESIA DALAM MEMANAJEMEN SUATU PERUSAHAAN - Lubis, Sadam Zulkhairi (CV. Pusdikra Mitra Jaya, 2025)
Leadership in Indonesia is a very relevant and interesting topic to research, considering that this country has a long and complex history in terms of political and organizational leadership. Since independence in 1945, Indonesia has been led by seven presidents, each with different characteristics and leadership styles. Each leader brought a vision and mission that influenced the direction of national policy and socio-political dynamics in society. In this study, the author used a literature review method. Literature research is a data collection technique that combines literature, books, notes, and reports related to the research topic. The ideal leadership model in Indonesia must be inclusive, adaptive, and focused on human development. Only with this kind of approach can leadership truly provide a positive and sustainable impact on society, organizations, and the nation as a whole. Leadership in Indonesia is a crucial aspect that affects various sectors of people's lives. The characteristics, styles, and challenges in leadership provide an overview of the complexity of a leader's role. This study shows that a participatory leadership style is more effective in improving organizational performance compared to an autocratic style. In addition, challenges such as socio-economic changes and bureaucracy need to be managed well so that leaders can carry out their duties effectively. The ideal leadership model must be able to accommodate the needs of society and be flexible in facing change.